Western Hemisphere : A Survey of Gender Budgeting Efforts - Perez Fragoso, Lucia (IMF Working Papers; Working Paper ;, 2016)
Gender budgeting is an approach to fiscal policy and administration that integrates considerations of women's equality and advancement into the budget. Latin American countries have undertaken diverse gender budgeting initiatives, most of them addressing public expenditures. This paper surveys and assesses some key initiatives, including those in Mexico, Mexico City, Ecuador, Bolivia, and El Salvador, and briefly summarizes others. The five key initiatives offer different perspectives on how countries approach gender budgeting. We find that these initiatives are contributing to the reduction of gender inequality and the advancement of women in Latin America, though there is scope to strengthen them.